Antibacterial Surfaces: Colloidal Gold Nanoclusters Spiked Silica Fillers in Mixed Matrix Coatings: Simultaneous Detection and Inhibition of Healthcare‐Associated Infections (Adv. Healthcare Mater. 6/2017). Issue 6 (March 2017) - Alsaiari, Shahad K.; Hammami, Mohammed A.; Croissant, Jonas G.; Omar, Haneen W.; Neelakanda, Pradeep; Yapici, Tahir; Peinemann, Klaus‐Viktor; Khashab, Niveen M.
Abstract : A smart antibacterial mixed‐membrane coating consisting of lysozyme@gold nanoclusters‐coated mesoporous silica nanoparticles encapsulating antibacterial agents in an amphiphilic polymer matrix is described by Niveen M. Khashab and co‐workers in article number 1601135. The membrane successfully senses and inhibites bacterial contaminations on X‐ray dental plates via a bacteria‐responsive controlled release mechanism. The monitoring of the contamination is simply visualized under UV‐light and demonstrated the applicability of the coating on biomedical devices.